Influence of oxygen flow vs. ambient annealing on microstructure and superconducting properties of YBa2Cu3O7−δ bulk ceramics - Mohamed Arebat, Ryad Alhadei; Awang Kechik, Mohd Mustafa; Kien, Chen Soo; Pah, Lim Kean; Baqiah, Hussien; Hong, Yap Siew; Shaari, Abdul Halim; Zailani, Thariez Hakim; Mohd Shariff, Khairul Khaizi; Shabdin, Muhammad Kashfi; Abdul Karim, Muhammad Khalis; Miryala, Muralidhar (Springer, 2025)
Optimizing annealing is crucial for enhancing the superconducting properties of high-temperature superconductors. This study investigates the effect of different annealing conditions on the superconducting properties of YBa2Cu3O7-δ (Y-123) bulk ceramics synthesized via a modified thermal decomposition (MTD) method. Two distinct samples were prepared: one was annealed in an oxygen flow, while the other was annealed under ambient conditions. Both samples were characterized using X-ray diffraction (XRD), Field emission scanning electron microscope (FESEM), and Four-point probe (4PP) techniques. XRD results confirmed the presence of the primary Y-123 phase in both samples, along with a minor secondary phase, demonstrating consistent phase formation and confirming an orthorhombic crystal structure across different annealing environments. FESEM analysis showed that annealing in an oxygen flow significantly increased grain sizes and amplified crystallographic defects, highlighting the crucial impact of oxygen levels on the structural integrity of the ceramics. Notably, 4PP measurements revealed that the sample annealed under ambient conditions exhibited a higher superconducting transition temperature (Tc-onset) of approximately 93.24 K, compared to 92.24 K for the sample annealed in oxygen flow. These findings suggest that ambient annealing in the MTD method not only enhances the superconducting properties of Y-123 ceramics but also offers a cost-effective, time-efficient alternative to oxygen flow during the sintering process.